The significance of plagioclase textures in mid-ocean ridge basalt (Gakkel Ridge, Arctic Ocean) - Bennett, Emma N.; Lissenberg, C. Johan; Cashman, Katharine V. (Contributions to Mineralogy and Petrology, 2019)
Textures and compositions of minerals can be used to infer the physiochemical conditions present within magmatic systems. Given that plagioclase is an abundant phase in many magmatic systems, understanding the link between texture and process is vital. Here, we present a database of textural and compositional data for > 1800 plagioclase crystals in mid-ocean ridge basalt from the Gakkel Ridge (Arctic Ocean) to investigate the physiochemical conditions and processes that govern the formation of plagioclase textures and compositions. The Gakkel basalts have high modal crystal contents (up to 50%). The crystal cargo is complex, with both individual plagioclase and glomerocrysts showing large variations in crystal habit, zoning and resorption. The most common types of zoning are reverse and patchy; we attribute patchy zoning to infilling following either skeletal growth or resorption. Resorption is abundant, with multiple resorption events commonly present in a single crystal, and results from both magmatic recharge and decompression. Periods of strong undercooling, distinct to quench crystallisation, are indicated by matured skeletal crystals and thin normally zoned melt inclusion-rich bands following resorption. Individual samples often contain diverse textural and compositional plagioclase groups. Furthermore, most plagioclase is not in equilibrium with its host melt. Finally, the porous open structures of some glomerocrysts suggest that they represent pieces of entrained disaggregated mush. We interpret this to indicate that the crystal cargo is not generally phenocrystic in origin. Instead, plagioclase crystals that formed in different parts of a mush-dominated plumbing system were entrained into ascending melts. The textures of individual crystals are a function of their respective histories of (under)cooling, magma mixing and decompression. The morphologies of melt inclusion trapped in the plagioclase crystals are associated with specific host crystal textures, suggesting a link between plagioclase ...